A SENSIBILIDADE DO OLHAR MULTIRREFERENCIAL ABRINDO CAMINHOS EM DIREÇÃO AO AUTOR-CIDADÃO - Albino, Jacqueline Meneguel (2008)
The study intends to discuss the concept of subject from the intersection of the ideas of autonomy, authorship and author-citizen as theoretical axis in order to investigate, through a multireferential approach, in what ways you can contribute to the formation of autonomous subjects considering the practice in a private confessional university. The subject, here, is not presented in the perspective of biological and physical body, but as a project, considered under historicity, sociability and, also, the human psyche. The purpose of this study is to analyze the subject´s formation in view of the educational proposal of UMESP METHODIST UNIVERSITY OF SAO PAULO. This option is justified mainly because the institution offers a differentiated educational proposal aimed at developing citizens. The concepts of institution and autonomy are very important to analyze in the context of this study the representations and the legitimate practices, as well the necessity of re-signification of the idea of citizenship, given the demands of contemporary life. Therefore, this is a qualitative exploratory research. The methodological procedures include participant observation and the application of a qualified route aiming to hearing students of the academic community. It was possible to clearly understand the intentions linked to confessionality portrayed in the UMESP Educational Project. Regarding the students intentions, there was concern about their professional formation. As per our understanding about the exercise of citizenship from the autonomy of the subject, we extended the observation to all the social actors involved. We noticed that it is possible to work towards the author-citizen because the student, in general, is opened to transforming himself. Relationship is the point. In fact it relates to how education happens. Teachers and students must find themselves as subjects in permanent construction, involved. Education can develop critical and independent people, subjects as authors of their own lives acting in accordance to their wishes and aware of their real needs and responsibilities.(AU)